CCL2 release by airway smooth muscle is increased in asthma and promotes fibrocyte migration. Issue 9 (16th June 2014) - Singh, S. R.; Sutcliffe, A.; Kaur, D.; Gupta, S.; Desai, D.; Saunders, R.; Brightling, C. E.
Abstract Background Asthma is characterized by variable airflow obstruction, airway inflammation, airway hyper‐responsiveness and airway remodelling. Airway smooth muscle (ASM) hyperplasia is a feature of airway remodelling and contributes to bronchial wall thickening. We sought to investigate the expression levels of chemokines in primary cultures of ASM cells from asthmatics vs healthy controls and to assess whether differentially expressed chemokines (i) promote fibrocyte (FC) migration towards ASM and (ii) are increased in blood from subjects with asthma and in sputum samples from those asthmatics with bronchial wall thickening. Methods Chemokine concentrations released by primary ASM were measured by MesoScale Discovery platform. The chemokine most highly expressed by ASM from asthmatics compared with healthy controls was confirmed by ELISA, and expression of its cognate chemokine receptor by FCs was examined by immunofluorescence and flow cytometry. The role of this chemokine in FC migration towards ASM was investigated by chemotaxis assays. Results Chemokine (C‐C motif) ligand 2 (CCL2) levels were increased in primary ASM supernatants from asthmatics compared with healthy controls. CCR2 was expressed on FCs. Fibrocytes migrated towards recombinant CCL2 and ASM supernatants. These effects were inhibited by CCL2 neutralization. CCL2 levels were increased in blood from asthmatics compared with healthy controls, and sputum CCL2 was increased in asthmatics with bronchial wall thickening. Conclusions Airway smooth muscle‐derived CCL2 mediates FC migration and potentially contributes to the development of ASM hyperplasia in asthma.